Universe and Inner Self in Early Indian and Early Greek Thought - Seaford, Richard (Edinburgh University Press, 2016)
From the sixth century BCE onwards there occurred a revolution in thought, with novel ideas such as such as that understanding the inner self is both vital for human well-being and central to understanding the universe. This intellectual transformation is sometimes called the beginning of philosophy. And it occurred - independently it seems - in both India and Greece, but not in the vast Persian Empire that divided them. How was this possible? This is a puzzle that has never been solved. This volume brings together Hellenists and Indologists representing a variety of perspectives on the similarities and differences between the two cultures, and on how to explain them. It offers a collaborative contribution to the burgeoning interest in the Axial Age and will be of interest to anyone intrigued by the big questions inspired by the ancient world.